The effect of progesterone concentrations during superovulation of Holstein heifers in a randomized trial - Marques, J. C. S.; Maciel, J. P. O.; Denis-Robichaud, J.; Conceicao, R. S.; Bega, A. M. [UNESP]; Moore, S.; Sirard, M. A.; Baes, C. F.; Cerri, R. L. A. (Elsevier B.V., 2023)
The aim of this study was to evaluate the effect of different progesterone (P4) concentrations during the follicular growth on the intensity of estrous expression, ovarian response to the superovulatory treatment, and embryo production and quality in superovulated heifers. A total of 63 Holstein heifers were randomly assigned into 2 experimental groups: Low P4 (n = 31) and High P4 (n = 32). Animals received a pre-synchronization protocol followed by a protocol of su-perovulation that included the allocated P4 treatment. Activity was monitored continuously by an automated activity monitor, and estrus characteristics (maximum intensity and duration) were recorded. Embryo col-lection was performed 7 d post artificial insemination (AI). Embryos were counted and graded from good or excellent (1) to degenerated (4). The outcomes of interest were: number and diameter of follicles at the time of AI, ovulation success (confirmed 7 d post-AI), time to estrus event, maximum intensity and duration of estrus, number and quality of embryos. Data were analyzed according to the type of outcome variable using logistic, linear, or Poisson regression models. A total of 105 embryos (High P4: n = 42; Low P4: n = 63) were graded for quality. Different P4 levels did not affect the maximum intensity (High P4 = 497.8 +/- 23.9%; Low P4 = 542.2 +/- 23.5%) or the duration (High P4 = 13.5 +/- 1.5 h; Low P4 = 14.3 +/- 1.4 h) of estrus. Heifers in the High P4 treatment had greater number of follicles at time of AI (High P4 = 16.6 +/- 1.6 follicles; Low P4 = 13.9 +/- 1.2 follicles), but with smaller diam-eter (High P4 = 11.3 +/- 0.1 mm; Low P4 = 12.0 +/- 0.1 mm) compared with Low P4. High P4 heifers tended to have better embryo quality compared with Low P4 heifers (odds ratio = 1.98; 95% CI = 0.90-4.35). High P4 heifers had less embryos than Low P4 heifers, but this was modified by the CIDR (intravaginal implant of P4) removal to estrus interval (interval 0-21 h: mean ratio = 1.15, 95% CI = 0.42-1.87; interval 22-46 h: mean ratio = 0.58, 95% CI = 0.27-0.96). Although estrous expression was not associated with embryo quality, as the duration and the maximum intensity of estrous expression increased, the number of embryos recovered 7 d post-AI increased (duration: mean ratio = 1.04; 95% CI = 1.03-1.05; maximum intensity: mean ratio = 1.50; 95% CI = 1.42-1.58). In conclusion, P4 during the follicular growth, and intensity of estrus, are playing a role in regulating the quality and the number of embryos produced by superovulated heifers. This study was supported by contributions from Resilient Dairy Genome Project and the Natural Sciences and Engineering Research Council.
Keywords: estrous expression; embryo quality; embryo production; dairy heifer